A longitudinal study on psychosocial causes and consequences of Internet gaming disorder in adolescence. Issue 2 (6th April 2018) - Wartberg, Lutz; Kriston, Levente; Zieglmeier, Matthias; Lincoln, Tania; Kammerl, Rudolf
Abstract: Background: In 2013, Internet gaming disorder (IGD) was incorporated in the current version of the DSM-5. IGD refers to a problematic use of video games. Longitudinal studies on the etiology of IGD are lacking. Furthermore, it is currently unclear to which extent associated psychopathological problems are causes or consequences of IGD. In the present survey, longitudinal associations between IGD and adolescent and parental mental health were investigated for the first time, as well as the temporal stability of IGD. Methods: In a cross-lagged panel design study, family dyads (adolescent with a parent each) were examined in 2016 (t1) and again 1 year later (2017, t2). Overall, 1095 family dyads were assessed at t1 and 985 dyads were re-assessed at t2 with standardized measures of IGD and several aspects of adolescent and parental mental health. Data were analyzed with structural equation modeling (SEM). Results: Male gender, a higher level of hyperactivity/inattention, self-esteem problems and IGD at t1 were predictors of IGD at t2. IGD at t1 was a predictor for adolescent emotional distress at t2. Overall, 357 out of the 985 adolescents received a diagnosis of IGD at t1 or t2: 142 (14.4%) at t1 and t2, 100 (10.2%) only at t1, and 115 (11.7%) only at t2. Conclusions: Hyperactivity/inattention and self-esteem problems seem to be important for the development of IGD. We found first empirical evidence that IGD could prospectively contribute to a deterioration of adolescent mental health. Only a subgroup of affected adolescents showed IGD consistently over 1 year.